2009
DOI: 10.1016/j.biopsych.2008.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment for Selectively Disrupting a Traumatic Memory via Postretrieval Inhibition of Glucocorticoid Receptors

Abstract: Background-Traumatic experiences may lead to debilitating psychiatric disorders including acute stress disorder and post-traumatic stress disorder. Current treatments for these conditions are largely ineffective; therefore, novel therapies are needed. A cardinal symptom of these pathologies is the re-experiencing of the trauma through intrusive memories and nightmares. Studies in animal models indicate that memories can be weakened by interfering with the post-retrieval re-stabilization process known as memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
57
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 74 publications
7
57
2
Order By: Relevance
“…Our results are consistent with several studies investigating reconsolidation blockers either systemically (Debiec and Ledoux, 2004;Blundell et al, 2008;Taubenfeld et al, 2009;Pitman et al, 2011) or intracranially (Nader et al, 2000;Debiec and Ledoux, 2004;Ben Mamou et al, 2006;Jin et al, 2007). Indeed, it is accepted in the literature that the lack of spontaneous recovery, the selectivity to reactivated memories, and the presence of intact short-term memory are criteria that define the reconsolidation process.…”
Section: Reconsolidation Specificitysupporting
confidence: 92%
“…Our results are consistent with several studies investigating reconsolidation blockers either systemically (Debiec and Ledoux, 2004;Blundell et al, 2008;Taubenfeld et al, 2009;Pitman et al, 2011) or intracranially (Nader et al, 2000;Debiec and Ledoux, 2004;Ben Mamou et al, 2006;Jin et al, 2007). Indeed, it is accepted in the literature that the lack of spontaneous recovery, the selectivity to reactivated memories, and the presence of intact short-term memory are criteria that define the reconsolidation process.…”
Section: Reconsolidation Specificitysupporting
confidence: 92%
“…These data strongly suggest that the experience of a traumatic event before fear acquisition strengthens fear memory formation and attenuates the degree of memory instability after retrieval (which becomes more evident in older memories). In support of the view that stronger memories are less vulnerable to disruption after recall, several authors showed that the increase in the number of footshock trials during fear acquisition produces a memory trace that is more resistant to interference after reactivation (Suzuki et al, 2004;Taubenfeld et al, 2009;Wang et al, 2009). It is widely accepted that several conditions constrain the occurrence of reactivation-induced instability and the subsequent development of memory reconsolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Interfering with the reconsolidation process provides an opportunity for disrupting memories that may contribute to the development of psychiatric disorders such as post-traumatic stress disorder (PTSD) or addiction (Dudai 2006;Diergaarde et al 2008;Taylor et al 2009). Recently, several pharmacological compounds have been tested in animal models of fear learning in order to identify drugs that can be potentially relevant for clinical trials of trauma-induced pathologies and, in particular, PTSD (Debiec and LeDoux 2006;Brunet et al 2008;Taubenfeld et al 2008). Particular attention has been given to blockers of stress hormones, including antagonists of glucocorticoid or b-adrenergic receptors.…”
mentioning
confidence: 99%
“…We previously reported that the glucocorticoid receptor antagonist RU38486 persistently disrupts inhibitory avoidance (IA) memory retention if administered either in the amygdala or systemically immediately following retrieval (Tronel and Alberini 2007;Taubenfeld et al 2008). Thus, we were interested in investigating the potential synergistic effect of blocking both glucocorticoid and b-adrenergic receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation